Neurocognitive sequela of burn injury in the elderly. (January 2019) - Esechie, Aimalohi; Bhardwaj, Anish; Masel, Todd; Raji, Mukaila
Highlights: Individuals over 65 years are predicted to grow in number in the next two decades. Age-related neurocognitive complications increases the risk of burn injury. Initiating rehabilitative efforts improves patients' mental and physical function. Abstract: Elderly individuals are a fast-rising segment of the US population and are at high risk of permanent disability and premature death secondary to traumatic injuries such as burn injury. The current paper will review the extant literature to understand the prevalence of burn injury in the elderly, the neurocognitive complications unique to the aged that places this cohort at risk, and evidence-based recommendations to reduce the early and late neurocognitive effects of burn injury in the aged. The elderly are a high-risk population for burn injury and its neurological sequela. This risk, at least in part, reflects multiple factors: age-related changes in the central and peripheral nervous system; multiple pre-existing co-morbidities (such as dementia and COPD); polypharmacy; suboptimal social support; and increased susceptibility to hypothermia, burn-related infections, and electrolyte and metabolic dysregulations.